Lecturer's Pedagogic Competence: Teaching English in Online Learning During Pandemic Covid-19 - Tira Nur Fitria (Journal of English Education, 2021)
This research is to describe the implementation of the lecturer's pedagogic competence in online English teaching at ITB AAS Indonesia during pandemic Covid-19. This research is descriptive qualitative. The result of the analysis shows that the implementation of a lecturer's pedagogic competence in online English teaching consists of three main competencies applied. First, 1) lecturer’s competence in preparing online learning. English lecturer prepares online learning by using e-learning institutions which can be accessed on http://elearning.itbaas.ac.id/. The English lecturer prepares a lecture contract, lesson plans, and syllabus for 1 semester, also teaching materials. The English lecturer also prepares the media of video conferencing in online learning. 2) lecturer’s competence in carrying out online learning. English lecturer teaching English online by using Zoom Meeting and YouTube Live Streaming. The recording and the streaming videos can be accessed on the English lecturer’s YouTube Channel. The students can join Zoom Meeting, YouTube Live Streaming, or both. 3) lecturer’s competence in evaluating online learning. English lecturer evaluates the students’ by giving tasks, mid-term and final tests in writing and reading which are shared in Google Classroom each class to evaluate students’ learning.